Optimal participation of ADN in energy and reserve markets considering TSO-DSO interface and DERs uncertainties - Chen, Houhe; Wang, Di; Zhang, Rufeng; Jiang, Tao; Li, Xue (Applied energy, 2022)
•Optimal market participation model of ADN in energy and reserve markets is developed.•The uncertainty of DERs and the interface of TSO and DSO are considered.•The problem of DSO’s strategic behavior is formulated as a stochastic bi-level optimization model.•The nonlinear bi-level model is converted into a mixed-integer second order cone programming (MISOCP) model. The flexibility of distribution networks continues to thrive due to the increasing installment of distributed energy resources (DERs). In addition to meeting the load demand in active distribution networks (ADNs), DERs can also provide energy and reserve for the upper-layer grid (i.e., sub-transmission network) at their connection node by participating in the energy and reserve markets. This paper proposes a novel optimal participation model of ADN in energy and reserve markets that takes into account the uncertainties of DERs and the interface of transmission system operator (TSO) and distribution system operator (DSO). The problem of DSO’s strategic behavior is formulated as a stochastic bi-level optimization model. The upper-level model indicates the market clearing of ADNs managed by the DSO and the lower-level model represents the energy and reserve market clearing of the upper-layer grid managed by the TSO. The nonlinear bi-level model is converted into a mathematical program with equilibrium constraint (MPEC) model, and then the mixed-integer second order cone programming (MISOCP) model based on Karush-Kuhn-Tucker conditions and strong duality theory. The effectiveness of the proposed model on improving the economy of ADN and the utilization rate of DERs is validated by numerical studies.